Violent and Nonviolent Terrorist Suspects: a Comparative Analysis Based on Data from the Netherlands - Thijs, Fabienne (European journal on criminal policy and research, 2024)
What are similarities and differences between violent and nonviolent terrorist suspects? Our study aims to answer this question by comparing violent terrorist suspects (VTS) (n = 57) to nonviolent terrorist suspects (NVTS) (n = 292) in the Netherlands. Guided by social control theories and using register data from the Dutch Public Prosecution Service, Statistics Netherlands, and the Research and Documentation Centre of the Ministry of Justice and Security, we investigated the 2 years leading up to the terrorist suspicion by examining demographic characteristics, household composition, socioeconomic factors, and criminal background. Findings demonstrate more similarities than differences between the groups. Nonetheless, VTS were significantly more often male and had more often a (violent) criminal background. For NVTS, we found possible preventive effects of living with parents and employment. Furthermore, the differences in socioeconomic status (SES) we found urge us to develop a better understanding of the socioeconomic environment VTS and NVTS are part of and whether and how their perception of this environment influences their behavior. Notwithstanding the limitations in our study (e.g., potential police bias in register data, small sample sizes), the analyses provide insight into what factors, and potential underlying mechanisms, need further investigation to understand violent and nonviolent outcomes.